The Israeli radical left : an ethics of complicity - Wright, Fiona, 1985- (Ethnography of political violence., 2018)
Fiona Wright traces the ethics and politics of radical Jewish Israeli leftwing activists who challenge the violence perpetrated by their state and in their name. She imparts the ways in which activists constantly negotiate their own condition of complicity and the impossibility of reconciling their principles with their everyday lives.